EFEKTIVITAS PIJAT LAKTASI TERHADAP KELANCARAN PRODUKSI ASI PADA IBU POST PARTUM DI PMB CARNIAH JAKARTA: Effectiveness Of Lactation Massage On The Effectiveness Of Breast Milk Production In Post Partum Mothers At PMB Carniah Jakarta - Nurjanah, Lindah; Rofika, Ana (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2023)
One of the efforts to reduce infant mortality is through the exclusive breastfeeding program. A new method introduced to prevent and overcome problems in breastfeeding is by doing lactation massage. Lactation massage is a new breakthrough in dealing with problems around breastfeeding. Lactation massage is a massage technique performed on the head or neck area, back, spine and breasts which aims to stimulate the hormones prolactin and oxytocin. This study aims to find out how the smoothness of milk production differs in Post Partum Mother Lactation Massage at PMB Carniah Jakarta. This type of research is quasi-experimental with Intact-Group Comparison. The population in this study were all postpartum mothers in September - November at BPM Carniah Jakarta, totaling 30 post partum mothers. As for the sampling technique using total sampling. The sample in this study consisted of 30 people consisting of 15 experimental groups (post partum mothers who were given lactation massage) with the criteria of post partum mothers being given lactation massage, namely on day 1 to day 14 for 15 minutes every day and 15 people in the control group (post partum mothers who were not given lactation massage). It can be concluded based on the results of the hypothesis test showing a p value of 0.041 <0.05 so that there is a difference in the smoothness of milk production in post partum mothers who are given lactation massage and those who are not given lactation massage at PMB Carniah Jakarta. It is hoped that health workers and health workers will introduce the concept of the importance of doing lactation massage to post partum mothers to support the fulfillment of exclusive breastfeeding for babies aged 0-6 months in the community by providing counseling to mothers once a month.